Role of Extracellular Vesicles in Glia-Neuron Intercellular Communication - Ahmad, Shahzad; Srivastava, Rohit K.; Singh, Pratibha; Naik, Ulhas P.; Srivastava, Amit K. (Frontiers in Molecular Neuroscience, 2022)
Cross talk between glia and neurons is crucial for a variety of biological functions, ranging from nervous system development, axonal conduction, synaptic transmission, neural circuit maturation, to homeostasis maintenance. Extracellular vesicles (EVs), which were initially described as cellular debris and were devoid of biological function, are now recognized as key components in cell-cell communication and play a critical role in glia-neuron communication. EVs transport the proteins, lipids, and nucleic acid cargo in intercellular communication, which alters target cells structurally and functionally. A better understanding of the roles of EVs in glia-neuron communication, both in physiological and pathological conditions, can aid in the discovery of novel therapeutic targets and the development of new biomarkers. This review aims to demonstrate that different types of glia and neuronal cells secrete various types of EVs, resulting in specific functions in intercellular communications.